Virtual worlds and criminality - Cornelius, Kai; Hermann, Dieter (Springer, 2011)
The fusion between virtuality and reality has created a new quality of experience establishing metaverses and virtual worlds. Second Life, Twinity, Entropia Universe or Fregger have experienced rapid growth in recent years and show no signs of slowing down. Not only have countless companies discovered these 'virtureal worlds' as marketplaces, but so have fraudsters and other criminals. In this book, European experts from different academic disciplines show how to meet the new challenges arising from virtual worlds. They discuss the reasons for and the impacts of these new forms of criminality as well as the necessity and means of combating them. Moreover, other fundamental issues are examined, such as the addictive potential of virtual-world use, media violence, and conflict resolution problems arising in the context of virtual worlds.